SHEET PILE CONSTRUCTION DESIGN AS AN ALTERNATIVE TREATMENT FOR LANDSLIDE ON THE CITY BOUNDARY’S ROADS SECTIONS OF TANAH GROGOT-LOLO KUARO, TANAH GROGOT DISTRICT, PASER REGENCY, TANA PASER - Cindy Nitasari; Markawie Markawie (Universitas Lambung Mangkurat, 2018)
In Tanah Grogot district, precisely on the KM 6 road which is the city boundary roads of Tanah Grogot City-Lolo Kuaro it has an important role as the only access for road users. Because at the side of the roads does not have a drainage channel, resulting in water overflowing and the seepage flowed on the surface, causing a landslide. The length of the landslides is 50 meters, with a width of 5.5 meters and the highest height is 9.6 meters. The result of this landslide is very disturbing for the road users. The delivery of goods and services can not be accommodated properly. Therefore, it is expected that this path must be handled properly, so the road can be functioning again safely and comfortably. How to handle this problem is by making a design of retaining walls construction which is safe in form of sheet pile.The planning for this anchored sheet pile begins with analyzing the secondary data in form of data sondir, laboratory data, and topographic measurement data. This then followed by the calculation of the forces acting on the sheet pile, the calculation of moments in the sheet pile, the calculation of the carrying capacity of the pile on the anchor, capacity calculations for the mast against a lateral load, and the slope stability analysis using GeoStudio2007 application. After that designing the sheet pile construction, tierod, the pile, planning the budget, and makes the Detail Engineering Design (DED).From the planning, the profile of concrete sheet pile obtained is CCSP W-500-A-1000 with a total length of the sheet pile is 12.2 meters. On tierod using dimensions of 6.32 m long with a diameter of 5 cm. On the pile is using a steel pipe with a diameter of 40 cm which penetrated into 10 m depth. For the stability of the slope with the reinforcement of piles obtained SF = 5.5> 1.25, which can be said as safe.Keywords: designing sheet pile, anchored sheet pile, steel pipe piles.